2017
DOI: 10.1002/jbm.a.36144
|View full text |Cite
|
Sign up to set email alerts
|

The penetration and phenotype modulation of smooth muscle cells on surface heparin modified poly(ɛ‐caprolactone) vascular scaffold

Abstract: The tubular porous poly(ɛ-caprolactone) (PCL) scaffold was fabricated by electrospinning. After then, the scaffold's surface was firstly eroded by hexyldiamine to endow amine group, and heparin was covalently grafted to the surface to get surface heparin modified scaffold (ShPCL scaffold). It was found that ShPCL scaffold can induce smooth muscle cells (SMCs) to penetrate the scaffold surface, while the SMCs cannot penetrate the surface of PCL scaffold. Subsequently, the rabbit SMCs were seeded on the ShPCL sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…In addition, it was found that heparin could inhibit SMC proliferation and upregulate the expression of contractile SMC phenotype markers [34]. Similar results have been reported in our previous studies as heparin-conjugated PCL scaffolds can induce SMC penetration through the scaffold surface while the SMCs cannot penetrate the surface of pure PCL scaffold [21]. Our study showed SMCs and collagen were the main components of neointimal formation (Fig.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In addition, it was found that heparin could inhibit SMC proliferation and upregulate the expression of contractile SMC phenotype markers [34]. Similar results have been reported in our previous studies as heparin-conjugated PCL scaffolds can induce SMC penetration through the scaffold surface while the SMCs cannot penetrate the surface of pure PCL scaffold [21]. Our study showed SMCs and collagen were the main components of neointimal formation (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…As the phosphorylation and calcium concentration change in the environment, calponin can regulate the binding of actins and myosin by capturing or releasing actins which could modulate the contraction and relaxation of SMCs. Therefore, the expression of calponin can be used to indicate the contractile phenotype of SMCs [21]. Our results exhibited that the coverage and area of the contractile SMCs increased during the course of 6 months and it indicated the grafts gradually remodeled to mimic the native aorta artery.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations